Enhancing Organizational Performance through COBIT 2019-Based IT Governance Audit: A Case Study of a Digital Technology Company - Setiadi, Laurentinus Heriyanto; Fianty, Melissa Indah (Journal of Information System and Informatics, 2024)
This study investigates the pivotal role of information technology (IT) governance in contemporary business landscapes, particularly emphasizing the digital technology sector. Through an examination of a digital technology company specializing in software development and fleet management platforms, the study utilizes the COBIT 2019 framework to conduct an IT governance audit. The research workflow, comprising planning, fieldwork, reporting, and result analysis stages, facilitates a comprehensive evaluation of the company's IT governance capabilities. Findings indicate proficiency in managed solutions identification and project management, alongside gaps in managing IT changes effectively. Recommendations are provided to address these gaps, emphasizing enhanced collaboration, documentation, and protocol establishment. By shedding light on IT governance practices within the digital technology sector, this study contributes to advancing organizational performance and competitiveness in an evolving landscape. Specifically, the recommendations align with the following domains: BAI03 (Managed Solutions Identification & Build), BAI06 (Managed IT Changes), and BAI11 (Managed Projects).